1999
DOI: 10.1359/jbmr.1999.14.9.1493
|View full text |Cite
|
Sign up to set email alerts
|

The Nucleolar Targeting Signal (NTS) of Parathyroid Hormone Related Protein Mediates Endocytosis and Nucleolar Translocation

Abstract: Previous work has identified the parathyroid hormone-related protein (PTHrP) nucleolar targeting signal (NTS) as both necessary and sufficient for localization of PTHrP to the nucleus and nucleolus of a variety of cells where it is believed to participate in the regulation of cell proliferation, differentiation, and apoptotic cell death. The mechanism whereby a secreted peptide, such as PTHrP, gains access to the nuclear compartment remains a question of debate. The current work examines the possibility that e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
56
0
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(62 citation statements)
references
References 42 publications
5
56
0
1
Order By: Relevance
“…These features allow PTHrP either to be secreted in a paracrine/autocrine fashion or to be retained within the cytosol and to be translocated to the nucleus (4,6,7). Alternative potential mechanisms of PTHrP entry into the cytosol have also been described (8)(9)(10).…”
Section: Ntranuclear Transport Of Numerous Polypeptide Ligands Has mentioning
confidence: 99%
“…These features allow PTHrP either to be secreted in a paracrine/autocrine fashion or to be retained within the cytosol and to be translocated to the nucleus (4,6,7). Alternative potential mechanisms of PTHrP entry into the cytosol have also been described (8)(9)(10).…”
Section: Ntranuclear Transport Of Numerous Polypeptide Ligands Has mentioning
confidence: 99%
“…However, Aarts and colleagues 36 demonstrated that the NLS-(87-107) alone was able to induce internalisation and nuclear localisation in chondrocytic cells. The differences between groups can be accounted for by the use of different cells lines, which is highlighted by differences seen in nuclear translocation of PTHrP-(1-34).…”
Section: Discussionmentioning
confidence: 99%
“…Although the presence of some other GPCRs at the nucleus has been reported (29, 46 -49), functionality has only been documented for PGE 2 and angiotensin II receptors (29,46,50); however, the latter peptide is not produced locally but possibly translocates to the nucleus as shown for parathyroid hormone and somatostatin (51,52). In contrast, PAF could be generated locally and act on its adjacent receptor in the nucleus (Figs.…”
Section: Discussionmentioning
confidence: 99%